SHARIA ECONOMIC STRATEGY TO REALIZE SUSTAINABLE DEVELOPMENT BASED ON GREEN ECONOMY - Sri Restu Mulawarman; Hasrul Zen; Mardhiyah Hayati (PT. Media Akademik Publisher, 2024)
Sustainable development as urgent world news, especially facing the challenges of climate change & environmental degradation. This concept emphasizes the importance of meeting the needs of the present generation without compromising the ability of future generations to meet their own needs. In this context, green economy emerges as an environmentally friendly & sustainable approach to economic growth. This type of research method is a qualitative literature review research that collects data using a search method based on a lot of examples of books, journals, & existing research. In this study, bibliographic analysis was conducted to find out a number of previous studies on the topic & literature related to green economic theory, Islamic economics, & SDGs. The tool used for the analysis is VOSviewer, & the key terms are green economy, Islamic economics, & SDGs. The results of this study Islamic Economics is based on Islamic principles & emphasizes the importance of environmental sustainability, environmental development can have a significant impact on economic and social progress. The Islamic economic perspective emphasizes the importance of reducing waste & pollution, which contributes to environmental sustainability. The Islamic economic approach is crucial to addressing environmental conflicts & creating a sustainable nation. The Islamic economic approach is crucial in encouraging Development.